Mapping and assessment of future changes in the coastal and marine ecosystem services supply in Lithuania - Inácio, Miguel (2022)
Assessing and mapping ecosystem services (ES) became an integral part of coastal and marine management practices. Hence, quantitative and validated approaches are lacking, especially to address future conditions. The objective of this study is to apply further existing and develop new methodological frameworks to quantitatively assess and map the current and future supply of 3 ES in the coastal zone of Lithuania: coastal flood protection, nutrient regulation, and maintenance of nursery conditions. For coastal flood ES modelling, 2 time periods (1990 and 2018) and 4 scenarios (A0, A1 A2, A3 - based on future socio-economic changes in Lithuania) were analysed. The coastal flood protection ES model was validated (r2 = 0.30) using tree cover density. The results showed spatial differences among the analysed periods but no statistical differences. High supply areas are located in the southern coastal area, while the central part displays a low supply. For nutrient regulation and maintenance of nursery conditions, 7 time periods were analysed: a historical period and 6 scenarios based on Representative Concentration Pathway 4.5 and 8.5 and 3 Shared Socioeconomic Pathways. The nutrient regulation ES model was validated (r2 = 0.85) using in situ nutrient. Statistical differences were observed for this ES, but a similar spatial distribution of high and low supply areas. A decrease in the supply was observed comparing the historical period and future scenarios. Maintenance of nursery conditions was validated (r2 = 0.72) based on the protection status of the coastal zone. Results show no statistical differences and similar spatial patterns among the periods. Rocky and sandbank areas show a high supply for this ES. Limitations of our work are mainly related to the resolution of the utilised indicators. Nevertheless, the information obtained from our models can support spatial planning and decision-making processes.